(untitled) (International Journal of Engineering and Computer Science, 2016)
In the present investigation, fatigue crack growth tests under mixed-mode (I and II) overload have been conducted on HSLA steel and subsequently genetic programming has been applied to predict post overload fatigue life. It is observed that the proposed model predicts fatigue life of HSLA steel with reasonable accuracy.